2007
DOI: 10.1007/s00259-006-0360-7
|View full text |Cite
|
Sign up to set email alerts
|

Regional CBF changes in Parkinson’s disease: a correlation with motor dysfunction

Abstract: ICA-based separation of normalized images into disease-related and disease-unrelated subspaces revealed many disease-related group blood flow differences. The regions revealed by ICA are consistent with the current model of PD. These rCBF changes in PD have not been fully demonstrated in any single functional imaging study previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…4,10,15,16,18,19,24,27) A cerebral blood flow study using technetium-99m hexamethylpropyleneamine oxime SPECT and SPM analysis 5,9,22,23) showed that cerebral blood flow was negatively correlated with the UPDRS part III scores in the parahippocampal gyrus, inferior parietal lobule, anterior cingulated gyrus, postcentral gyrus, and insular area. 1,2,[12][13][14] These observations were consistent with our findings.…”
Section: Discussionsupporting
confidence: 83%
“…4,10,15,16,18,19,24,27) A cerebral blood flow study using technetium-99m hexamethylpropyleneamine oxime SPECT and SPM analysis 5,9,22,23) showed that cerebral blood flow was negatively correlated with the UPDRS part III scores in the parahippocampal gyrus, inferior parietal lobule, anterior cingulated gyrus, postcentral gyrus, and insular area. 1,2,[12][13][14] These observations were consistent with our findings.…”
Section: Discussionsupporting
confidence: 83%
“…For example, the performance of novelty seeking in patients with PD correlated with the insular cortical dopamine D2 receptor availability [Kaasinen et al, 2004]. In addition, the regional cerebral blood flow (rCBF) in the insula decreases in PD [Hsu et al, 2007;Kikuchi et al, 2001], and is negatively correlated with the motor UPDRS [Hsu et al, 2007]. It has been suggested that the insular hypoperfusion has a relation with disease severity and participates in motor performance, and is consistent with the extended predictions of the basal ganglia circuit model [Hsu et al, 2007].…”
Section: Cmentioning
confidence: 80%
“…Inhibition of inherent response tendencies is, in fact, considered one of the core functions of DLPFC [17,27,32]. Therefore, and in view of the many reports of a dysfunction of DLPFC in PD [3,12,23,41], a disruption of the interplay between the basal ganglia and DLPFC would seem to be the most likely cause of the patients' anticipatory behaviour. This view fits with the observation that the most severe depletion of dopamine occurs in those areas of the caudate that are connected to DLPFC [37].…”
Section: Discussionmentioning
confidence: 94%